The palatal septal cartilage implantation for snoring and obstructive sleep apnea. Issue 6 (December 2018) - Lee, Yi-Chan; Lee, Li-Ang; Li, Hsueh-Yu
Abstract: Objective: Patients with snoring and obstructive sleep apnea frequently have nasal and palatal obstruction. The objective of this study was to investigate the safety and feasibility of a palatal septal cartilage implant (SCI) for snoring and obstructive sleep apnea. Methods: This was a preliminary study of 10 consecutive patients who were enrolled retrospectively from electronic charts. The patients had undergone a single-stage operation including septoturbinoplasty and palatal SCI at a tertiary referral hospital. After nasal surgery, the harvested cartilage was prepared and trimmed into strips for palatal implantation. Key procedures of palatal SCI include vertical tunneling of the midline and paramedian soft palate, insertion of the septal cartilage strips, and fixation suture of the implants. The primary outcome measures were adverse events, including implant extrusion, infection, bleeding, velopharyngeal insufficiency and globus symptoms, assessed by the Glasgow–Edinburgh Throat Scale (GETS) questionnaire (10-item, 8-grade [0–7] Likert scale). Secondary outcomes were subjective snoring loudness (visual analogue scale, VAS), excessive daytime sleepiness (Epworth sleepiness scale, ESS) and objective apnea-hypopnea index. All patients were followed up for at least 1 year. Results: None of the aforementioned adverse events were noted during the one-year follow-up. Among the ten items of the GETS, the median score of nine items was 0, and the median score of the total GETS was 2.0, which was classified as "asymptomatic". The snoring loudness improved significantly from 8.0 points (IQR 8.0–9.0) preoperation to 4.0 points (IQR 2.5–6.0) at 3 months postoperation and 4.5 points (IQR 3.3–6.0) at 1 year postoperation ( P = 0.002 and P = 0.002, respectively). The ESS score improved significantly from 11.5 points (IQR 8.3–18.5) preoperation to 8.0 points (IQR 6.3–10.8) at 3 months postoperation and 8.5 points (IQR 6.3–10.8) at 1 year postoperation ( P = 0.004 and P = 0.004, respectively). The apnea-hypopnea index significantly decreased from 54.7 (IQR 23.4–62.8) to 20.5 (IQR 14.7–45.6) ( P = 0.047) in patients with a lower tongue position (modified Mallampati class ≤ II; n = 7). Conclusion: Palatal SCI is a safe and feasible procedure. The advantages include providing implants of tailor-made length, biocompatible autologous cartilage and no need for extra-payment for the implant material. By using the SCI procedure, both nasal obstruction and sleep-disordered breathing can be managed in a single-stage operation. The long-term effectiveness of SCI deserves further research.